Politeness Strategies Used by the Indonesian Minister of Foreign Affairs in a Speech at the General Debate of the United Nations: Pragmatics Study - Almora, Solleil Bellini; Heryono, Heri (Universitas Nahdlatul Wathan Mataram, 2025)
This study analyzes the politeness strategies employed by Indonesian Foreign Minister Retno Marsudi during her speeches at the 78th United Nations General Debate. The research employs a qualitative method for data collection, utilizing speech transcripts as primary data sources. Data analysis is conducted through thematic analysis, identifying and categorizing the politeness strategies based on Brown and Levinson's politeness theory. To ensure data validity, triangulation is applied by cross-referencing the findings with expert opinions in the field of diplomatic communication. The research identifies four primary strategies: Positive Politeness, Bald-On Record, Negative Politeness, and Off-Record. Each strategy serves distinct contexts and purposes, reflecting the minister's diplomatic approach. The findings reveal that Retno Marsudi effectively utilizes these strategies to convey significant messages while considering factors such as social distance, ranking of imposition, and power dynamics in international relations. Notably, the study highlights the predominant use of Positive Politeness Strategy, which fosters solidarity and cooperation among nations. The implications of this research suggest that understanding politeness strategies can enhance diplomatic communication and foster better international relations, emphasizing the importance of cultural sensitivity in global discourse.